Ujaran Kebencian di Media Sosial Instagram dan Tiktok: Studi Sikap Mahasiswa IAIN Manado - Hassan, Fidia (Jurnal JINNSA (Jurnal Interdipliner Sosiologi Agama), 2025)
The rapid expansion of social media has transformed digital platforms into new public spheres that enable massive interaction and expression, while simultaneously generating serious challenges such as the proliferation of hate speech. This article aims to analyze the attitudes of students at IAIN Manado toward hate speech on Instagram and TikTok and to examine the factors influencing these attitudes. This study employs a qualitative approach with a field research design. Data were collected through in-depth interviews, observation of social media activities, and documentation involving ten purposively selected students. Data analysis was conducted through data reduction, thematic categorization, and interpretative analysis by linking empirical findings with theories of attitude, social action, and the digital public sphere. The findings reveal that students generally possess a good level of knowledge regarding hate speech, although the depth of understanding varies according to academic background. Students’ attitudes toward hate speech can be categorized into three main patterns: active rejection, adaptive caution, and permissive attitudes. These attitudes are influenced by digital literacy, religious values, local cultural norms, social media experiences, and concerns over the chilling effect. This study emphasizes that hate speech on social media should not be understood merely as individual expression, but as a structural phenomenon embedded within the dynamics of the digital public sphere shaped by algorithms and commercial logics. Therefore, addressing hate speech requires a multidimensional approach that integrates legal frameworks, digital literacy education, communication ethics, and the strengthening of religious moderation values within higher education institutions.